Hepatopancreatoduodenectomy in North America: are the outcomes acceptable?. Issue 3 (March 2020) - Welch, Jonathan C.; Gleeson, Elizabeth M.; Karachristos, Andreas; Pitt, Henry A.
Abstract: Background: Hepatopancreatoduodenectomies (HPD) are historically associated with high morbidity and mortality. Currently, no data with hepatopancreatobiliary-specific complications have been available for HPD in North America. The aim of this retrospective analysis was to compare the outcomes of HPD to those of major hepatectomy (MH) and pancreatoduodenectomy (PD) in North America. Methods: The 2014-16 American College of Surgeons-National Surgical Quality Improvement Program database was queried for MH, PD, and HPD. Partial hepatectomies, wedge liver biopsies, distal pancreatectomies, pancreatic enucleations and total pancreatectomies were excluded. Propensity score matching was utilized to match 23 HPDs to 92 MHs and 138 PDs by 28 demographic, comorbidity, laboratory, operative and pathologic variables. Outcomes were compared among these three groups. Results: The overall morbidity and mortality for HPD were 87% and 26%, respectively, and were significantly higher (p < 0.01) compared to both MH (51%, 7.6%) and PD (52%, 1.4%). Post-hepatectomy liver failure (PHLF) was more common (p < 0.01) in HPD patients, but pancreatic fistula rates were similar. Conclusion: The morbidity and mortality after HPD are significantly higher than after MH or PD alone and may explain why HPD is performed so infrequently in North America. Centralization of HPD to a very few centers may be a strategy to improve outcomes.